PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI KALIMANTAN SELATAN - APSIFLAVIANA RIWUT WINEY; SYAHRITUAH SIREGAR (PPJP Universitas Lambung Mangkurat, 2019)
This study aims to determine how the influence of infrastructure development on economic growth in south kalimantan, and to find out which infrastructure is most influential on economic growth in south kalimantan. Infrastructure as the factor of production in this study is represented by road infrastructure, electricity infrastructure, and water infrastructure. Whereas economic growth is represented by gross regional income variable. This study uses panel data with the aim of getting the Best Linear Unbiased Estimator results, the results show a Fixed Effect Model that best fits the conditions of the data to help get the expected analysis results. The final results of this study states that two of the three independent variables positively and significantly affect the dependent variable. That two variables are electricity infrastructure and water infrastructure, while the road infrastructure has a positive effect but not significant towards economic growth in South Kalimantan, and the infrastructure that most influences economic growth is electricity infrastructure.Keywords: Road Infrastructure, Electricity Infrastructure, Water Infrastructure, Economic Growth